Pendidikan Politik Dalam Perspektif Qur`An: Implementasi Pembentukan Budaya Politik Masyarakat Beradab - Faelasup (Jurnal Ilmu Sosial dan Humaniora, 2023)
Research with the title political education in the perspective of the Qur'an: The implementation of the political culture of a civilized society is motivated by the increasingly sharp political conditions in Indonesia, so that the political aspirations conveyed by the community have seen the capacity of political channels (political parties) in society. The focus of his research is 1) The perspective of the Qur'an, 2) Channels of political education in society, 3) Building a political culture of a civilized society . The research method is library research with literature study, articles, scientific journals, and searches on qur`an interpretations related to political issues. The results of research 1) The perspective of the qur`an, that is, in tracing the Qur'an, verses that reveal political problems are found. In Islam it is known as fiqih siyasah, which is legal knowledge derived from the Al-Qur`an and Sunnah. 2) Channels of political education have two things, firstly formal education, namely political education through formal schools, the second is community education carried out by political parties towards the community. 3) Building a political culture of a civilized society, there are many verses that lead to the formation of a political culture of a civilized society through party cadre and party socialization